2017
DOI: 10.3892/ol.2017.5630
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD146 in combination with vorinostat for the treatment of ovarian cancer cells

Abstract: Drug resistance is the predominant cause of mortality in late-stage patients with ovarian cancer. Histone deacetylase inhibitors (HDACis) have emerged as a novel type of second line drug with high specificity for tumor cells, including ovarian cancer cells. However, HDACis usually exhibit relatively low potencies when used as a single agent. The majority of current clinical trials are combination strategies. These strategies are more empirical than mechanism-based applications. Previously, it was reported that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…Under pathological conditions, such as inflammation and tumorigenesis, CD146 was upregulated in the related cells and has been identified as a reliable marker for numerous types of cancers. Accumulating evidence shows that CD146 overexpression has been linked to either the initial development of the primary lesion or progression to metastases of most of cancer types, primarily including melanoma, 1,27-29 breast, 6,30,31 ovarian, [32][33][34][35] lung, 36,37 prostate, [38][39][40] glioma, 41 kidney, 42 hepatic, 43,44 and gastric cancers. 21,45 In 2017, Nollet et al reported that TsCD146 mAb (for tumor specific anti-CD146 monoclonal antibody) can specifically recognize CD146 expressed in cancer cells but not CD146 in physiological vessels, suggesting that structural features of cancer CD146 differ from those of physiological CD146.…”
Section: The Expression Profile Of Cd146 Proteinmentioning
confidence: 99%
“…Under pathological conditions, such as inflammation and tumorigenesis, CD146 was upregulated in the related cells and has been identified as a reliable marker for numerous types of cancers. Accumulating evidence shows that CD146 overexpression has been linked to either the initial development of the primary lesion or progression to metastases of most of cancer types, primarily including melanoma, 1,27-29 breast, 6,30,31 ovarian, [32][33][34][35] lung, 36,37 prostate, [38][39][40] glioma, 41 kidney, 42 hepatic, 43,44 and gastric cancers. 21,45 In 2017, Nollet et al reported that TsCD146 mAb (for tumor specific anti-CD146 monoclonal antibody) can specifically recognize CD146 expressed in cancer cells but not CD146 in physiological vessels, suggesting that structural features of cancer CD146 differ from those of physiological CD146.…”
Section: The Expression Profile Of Cd146 Proteinmentioning
confidence: 99%
“…Ischemic cerebrovascular disease (ICD) refers to a group of clinical syndromes arising from cerebral circulatory dysfunction of various causes, and brain damage and neurological dysfunction of patients caused by cerebral ischemia, hypoxia and necrosis at the associated blood vessel zone (1). The incidence rate of ICD among cerebrovascular diseases is ~70% in China (2).…”
Section: Introductionmentioning
confidence: 99%
“…According to the data of one survey, it possesses the highest disability and mortality rate in China (4). The incidence rate is rising at an annual growth rate of 8.7%, reflecting China's aging population (1).…”
Section: Introductionmentioning
confidence: 99%
“…The first HDACi, SAHA (Vorinostat, Zolinza ™ , Merck & Co, Inc., USA), was approved by FDA in 2006, and since then, HDACi are being developed for the treatment of T-cell lymphoma (194)(195)(196) and multiple myeloma (197). Furthermore, other studies and clinical trials showed the effects of Vorinostat in hematological and solid cancers including pancreatic (198), ovarian (199), prostate (200), and breast cancer (201).…”
Section: Histone Deacetylase Inhibitors (Hdaci)mentioning
confidence: 99%